GENETIC DIVERSITY OF WHEAT CULTIVARS ESTIMATED BY SSR MARKERS - K. Dvojković; G. Drezner; D. J. Somers; Z. Šatović; D. Horvat; D. Novoselović; A. Lalić (Poljoprivreda, 2008)
Presence and utilization of the genetic variability in the breeding programmes is prerequisite for their successfulness. Important factor for crop improvement is knowledge about the genetic diversity which providing a basis for the precise selection of parental combinations. Since beginning of 20th century, generation of wheat breeders and scientists in Croatia developed numerous advanced and successful wheat cultivars. Previous researches aimed to genetic diversity evaluation in Croatia were conducted by means of morphological traits, pedigree data (coefficients of parentage), proteins (glutenins and gliadins) and RAPD DNA markers. DNA markers detect directly variation of DNA sequence for particular loci and they are not under influence of environment, epistatic and pleiotropic effects. Microsatellite markers (Simple Sequence Repeats; SSRs), as highly polymorphic, informative and codominant DNA marker system, have been extensively used for genetic diversity studies on wheat world wide. A set of 98 wheat cultivars released in Croatia during the period 1905-2007, and 24 foreign cultivar (included because of their ancestral significance or as standards), were screened by 45 microsatellite markers, covering all three wheat genomes. The objectives of this study were to evaluate the microsatellites-based genetic diversity with emphasize on cultivars created at the Agricultural Institute Osijek, as well as to investigate SSR application for selection of genetically the most distant parental pairs. Preliminary data obtained by means of SSR markers showed a satisfactory level of genetic diversity and usefulness of microsatellites for parental selection.